PENGARUH KERJASAMA TIM DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PT PRIME LOGISTICS JAKARTA SELATAN - Safiih, Abdul Rahman; Safitry, Hilda Melinia (Journal of Research and Publication Innovation, 2024)
The purpose of this study to determine the effect of teamwork and work discipline on employee performance at PT Prime Logistics South Jakarta. The method used is a descriptive method with an associative approach. The sample collectiontechnique in this research was a saturated sample with a sample of 61 respondents. Data analysis uses regression analysis, correlation coefficient analysis, coefficientof determination analysis and hypothesis testing. The results of this research are that teamwork has a positive and significant effect on employee performance by 83.2%. Partially testing the hypothesis obtained t count > t table or (17.094 > 2,001), so that H0 is rejected and H1 is accepted, meaning that there is a positive and significant influence between teamwork (X1) on employee performance (Y) at PT Prime Logistics South Jakarta. Work discipline has a positive and significant effect on employee performance by 70.7%. Partially testing the hypothesis obtainedt count> t table or (11,930 > 2,001), so that H0 is rejected and H2 is accepted, meaning that there is a positive and significant influence between work discipline (X2) on employee performance (Y) at PT Prime Logistics South Jakarta. Simultaneous hypothesis testing: Teamwork and work discipline have a positive and significant effect on employee performance with a coefficient of determinationof 85.6% while the remaining 14.4% is influenced by other factors. Hypothesis testing obtained a calculated F value > F table or (171.843 > 3,16), thus H0 was rejected and H3 was accepted. This means that there is a simultaneous positive andsignificant influence between teamwork and work discipline on employee performance at PT Prime Logistics South Jakarta.